2014
DOI: 10.1080/07448481.2014.945456
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Number of Fast Food Meals Obtained by College Meal Plan Students

Abstract: Increasing levels of health consciousness and reducing access to fast food restaurants through flex plans may reduce college students' consumption of fast food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
19
1
3
Order By: Relevance
“…Although fast food is pervasive and easily accessible on and around college campuses, there is some evidence that student fast food consumption might be reduced via manipulation of meal plan components. One cross‐sectional study found that students with higher on‐campus meal allowances ate less fast food, and students who had ‘flex dollar’ access to fast food restaurants ate more fast food 32 . This suggests dining plans that offer more dining meals and limit use of points for restaurant purchases might reduce student fast food consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Although fast food is pervasive and easily accessible on and around college campuses, there is some evidence that student fast food consumption might be reduced via manipulation of meal plan components. One cross‐sectional study found that students with higher on‐campus meal allowances ate less fast food, and students who had ‘flex dollar’ access to fast food restaurants ate more fast food 32 . This suggests dining plans that offer more dining meals and limit use of points for restaurant purchases might reduce student fast food consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Questions that measured student behavior within the college foodscape included typical time traveled to reach food options on campus (Bader, Purciel, Yousefzadeh, & Neckerman, 2010;Calvez et al, 2016;Dingman, Schulz, Wyrick, Bibeau, & Gupta, 2014), factors considered to be most important (e.g., price, menu, available time, location, local ingredients, buying/eating with others, and SNAP/WIC acceptance) when making on-campus food selections (Graham, Pelletier, Neumark-Sztainer, Lust, & Laska, 2013), and types of food venues most frequently visited. Eleven main categories of food outlets were identified via direct inspection and an on-campus audit of the local food environment: vending machines, campus cafeteria, campus café, food pantry, bodegas (small corner stores selling mostly food items 1 ), supermarkets, convenience stores, fast food restaurants, food carts, sit-down restaurants, and all-you-can-eat buffets.…”
Section: Survey Measuresmentioning
confidence: 99%
“…This behavior mirrors that of other countries such as USA, where students on university campuses consume fast food approximately 3–8 times per week. [56]…”
Section: Introductionmentioning
confidence: 99%